Efektivitas Model Genre Based Approach Berbantuan Media Teks Pidato dalam Peningkatan Kemampuan Menulis Teks Pidato Siswa SMPN 3 Karawang Barat - SEPTIANI SHOBIHAH; WIENIKE DINAR PRATIWI; SLAMET TRIYADI (EDU-KATA, 2026)
This study aims to determine the effectiveness of the Genre Based Approach learning model assisted by speech text media on the speech writing ability of class VIII students of SMPN 3 Karawang Barat. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. Data collection was carried out through a speech writing ability test given before and after treatment. Data were analyzed using relevant statistical tests to determine differences in student learning outcomes. The results showed that the application of the Genre Based Approach model assisted by speech text media had a positive effect on students' speech writing ability. Students who participated in learning using this model showed a better improvement in writing ability compared to students who participated in regular learning. Genre Based Approach assisted by speech text media can be used as an effective learning alternative in improving students speech writing ability.